Reduced graphene oxide–transition metal hybrids as p-type semiconductors for acetaldehyde sensing. Issue 6 (20th April 2016) - Murashima, Yusuke; Karim, Mohammad Razaul; Furue, Ryo; Matsui, Takeshi; Takehira, Hiroshi; Wakata, Kosuke; Toda, Kei; Ohtani, Ryo; Nakamura, Masaaki; Hayami, Shinya
Abstract : Reduced graphene oxide–transition metal hybrids were accomplished to deposit a p-type semiconductor films on conductive glass for acetaldehyde sensing. Abstract : Acetaldehyde gas sensing using hybrids of reduced graphene oxide (rGO) and transition metal elements, rGO–M (M = oxide/hydroxide of Mn, Fe, Co and Ni) has been investigated. Thin films of GO, rGO and rGO–M on conductive glass were deposited through simple and affordable techniques and characterized using Raman spectroscopy, powder X-ray diffraction patterns, field emission scanning electron microscopy and electrical conductivity measurements. Concentration dependent resistances during the oxidation of acetaldehyde gas in air (10 to 50%) were investigated by using a sensing probe devised from rGO, GO–M and the rGO–M hybrids, of which rGO–Ni exhibited the maximum sensitivity. In rGO–Ni, in combination with rGO the NiOOH precursor can capture electrons (generated from acetaldehyde oxidation) through the holes, while indicating rGO–Ni to be a p-type semiconductor. This report implies the possibility of developing inexpensive graphene based p-type semiconductors for sensing other gases as well.